2014
DOI: 10.1590/1982-021620140412
|View full text |Cite
|
Sign up to set email alerts
|

Ruído e seus impactos nos hospitais brasileiros: uma revisão de literatura

Abstract: O aumento dos níveis de ruído nos hospitais, atribuído a diferentes fatores, dentre eles a grande incorporação de tecnologias, a concentração e o fluxo de pessoas e a não observância do silêncio pela própria equipe de trabalho e usuários do serviço, pode impactar negativamente no processo de trabalho e na saúde de profissionais e usuários. Este estudo teve como objetivo realizar revisão de literatura nacional sobre ruído em serviços hospitalares no Brasil, analisando aspectos referentes à produção científica, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…This emphasizes the importance of team training, good work practices, and the need for management and hospital equipment maintenance, in order to reduce noise levels 9 .…”
mentioning
confidence: 99%
“…This emphasizes the importance of team training, good work practices, and the need for management and hospital equipment maintenance, in order to reduce noise levels 9 .…”
mentioning
confidence: 99%
“…Workers' critical awareness on general hazards and noiserelated hazards by means of prevention programs including educational interventions with active learning methodologies, is paramount for the promotion of hearing and general health. Educational activities are carefully planned with strategies and dynamics that allow workers to be protagonists, thus facilitating the educational process (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Research studies carried out in hospital settings showed the existence of several occupational hazards, among them physical hazards, such as noise and its effect on hearing, uncovering the need of implementing hearing conservation programs (4,5,6,7,8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pode-se inferir que, nesta amostra, a maioria dos pacientes idosos não percebeu o ruído ambiental como muito incômodo, mesmo que se considere que o nível de ruído de muitos dos hospitais brasileiros esteja acima dos padrões recomendados e possam acarretar respostas fisiológicas ao estresse, sobretudo em hospitais universitários, que contam com maior número de equipamentos e circulação de pessoas 42,43 .…”
Section: Discussionunclassified